The Influence of Corporate Social Responsibility, Social Media Marketing, Sales Promotion, and Perceived Value on Consumer Purchase Decision on the Tokopedia Marketplace - Indah Mawarni; Oktafalia Marisa Muzammil (Dinasti Publisher, 2023)
The development of technology and the internet encourages changes in consumer behaviour, where currently the majority of consumers in Indonesia often shop online through a marketplace. Thus, competition between marketplaces is getting tougher to dominate the digital economy market in Indonesia. The purpose of this study is to determine the Influence of Corporate Social Responsibility, Social Media Marketing, Sales Promotion, and Perceived Value on Consumer Purchase Decision on the Tokopedia Marketplace. The population representative in this study is 178 samples that will be further processed through several tests with IBM SPSS Statistics 24 software. The results of this study found that Social Media Marketing and Perceived Value have a significant effect on Purchase Decision. Meanwhile, Corporate Social Responsibility and Sales Promotion do not have a significant effect on Purchase Decision.